Evaluasi Skrining Resep Dan Pelayanan Informasi Obat (PIO) Pasien Rawat Inap - Abas, Achmad Fadli; Yulianti, Yulianti; Fauziah, Siti Nur (PHRASE (Pharmaceutical Science) Journal, 2025)
Clinical pharmacy services are an important component of the health care system that aims to ensure patient safety. Clinical pharmacy services include various activities, including prescription screening and drug information services. This study aims to determine the results of the evaluation of the implementation of prescription screening and drug information services for inpatients at Grha Permata Ibu Hospital. This study is a descriptive observational study conducted with a retrospective data collection method. Data were obtained from inpatient prescriptions received at Grha Permata Ibu Hospital during the period October to December 2024. The samples used in this study amounted to 206 prescription sheets. Based on the results of the study, prescription screening based on administrative completeness has been carried out quite well in accordance with the provisions stated in Permenkes No. 72/2016, with an average achievement of 70.13%. Prescription screening based on pharmaceutical suitability showed excellent results with an average percentage of 93.93%. In addition, drug information services have also been implemented well, with an average achievement of 87.54%.